Interpretasi Tokoh Agama Tentang Pentingnya Pemahaman Manajemen Emosional di Masa Krusial 1 Sampai 5 Tahun Awal Pernikahan dalam Urgensi Preventif Perceraian di Kec. Patumbak - Mutiara, Dwi Utamika; Huda Prasetiya, Nurul; Affandy, Arif (LPPM Universitas Ekasakti Padang, 2023)
Marriage is one of the developmental tasks of the younger generation. Newlyweds' expectations are often not met in the early stages of marriage, which can even lead to a difficult adjustment period for both parties. Therefore, managing emotions during this period is very important for the quality of the marriage in the future. Lack of emotional maturity at the start of marriage can cause conflict and even lead to divorce. Good emotional management in the early stages of marriage is very necessary to prevent divorce. The focus of this research is to determine the importance of emotional management in the early stages of marriage, divorce factors, and forms of emotional management, using a qualitative approach and a case study approach. Data collection techniques were carried out through an interview process. The findings show that understanding emotion management in the first 1 to 5 years of marriage is important for preventing divorce.